2020
DOI: 10.3390/molecules25112716
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Fatty Acid-Induced Conformational Transitions and Aggregation of the Repeat Domain of Tau

Abstract: Background: The intrinsically disordered, amyloidogenic protein Tau associates with diverse classes of molecules, including proteins, nucleic acids, and lipids. Mounting evidence suggests that fatty acid molecules could play a role in the dysfunction of this protein, however, their interaction with Tau remains poorly characterized. Methods: In a bid to elucidate the association of Tau with unsaturated fatty acids at the sub-molecular level, we carried out a variety of solution NMR experiments in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…The role(s) of anions in tau self-assembly have remained elusive. Many pioneering manuscripts have shown that individual polyanions promote this process 22,27,33,47,48 , with the most attention placed on heparins and polyphosphates. Here, we expand the landscape of tested anions, with a special focus on those naturally occurring ones that tau might encounter in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The role(s) of anions in tau self-assembly have remained elusive. Many pioneering manuscripts have shown that individual polyanions promote this process 22,27,33,47,48 , with the most attention placed on heparins and polyphosphates. Here, we expand the landscape of tested anions, with a special focus on those naturally occurring ones that tau might encounter in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid membranes promoted Tau self-assembly at the membrane surface. 145,451 MTBR was identified as a lipid-binding domain, 452,453 with interactions specifically mediated by the PHF6 region. 454 Lipid membranes were found to induce a shift in full-length Tau molecular conformation towards b-sheet-containing structures, that formed stable oligomeric complexes.…”
Section: Is Heparin a Major Structural Component Of Tau Fibrils?mentioning
confidence: 99%
“…Interaction with phospholipids or free fatty acids can also induce the aggregation of full-length tau (62, 130) or a tau fragment comprising the MBR (131). Interestingly, it has also been reported that the NTR can contribute to tau polymerization because a disease-associated R5L mutation in the NTR increases tau polymerization (132).…”
Section: Pathological Changes Of the Interactions Of The Microtubule Binding Regionmentioning
confidence: 99%